Use of eDNA and conventional sampling methods to survey rock pool (gnamma) biodiversity on granite inselbergs - Michael, Damian R.; Murray, Allan; Murray, Phil; Murray, Beau; Hagen, Sam; Mcternan, Richard; Furst, Deborah J.; Nimmo, Dale G. (Austral ecology, 2024)
Sampling of environmental DNA (eDNA) and high‐throughput sequencing is emerging as an effective biodiversity assessment method in aquatic systems and may have utility for biodiversity inventory in terrestrial environments. Rock pools (gnammas) on granite inselbergs support a rich community of aquatic organisms and are culturally important to Indigenous peoples worldwide. However, the application of eDNA to survey rock pool biodiversity are undocumented. In a collaborative study with traditional owners, we explore the application of eDNA metabarcoding and traditional sampling methods to document and compare species richness and composition of eukaryotes from 15 rock pools (pits and pans) on granite inselbergs in southeastern Australia. We detected 116 taxonomic units, 81 assignments from eDNA sequencing and 35 species (23 rotifers and 12 microcrustaceans) using microscopic analysis. eDNA detected a broad range of taxa not previously documented from rock pools in Australia, although significantly more zooplankton (rotifers and microcrustaceans) were detected under a microscope, including several rare species and two undescribed species of rotifer. Brachionus calyciflorus and B. angularis were the only rotifer species assigned to species level through eDNA sequencing and were detected using both methods. We found no significant difference in mean species richness between rock pool types; however, species composition differed significantly between pits and pans. This study highlights the value of using eDNA to document biodiversity of ephemeral aquatic habitats in terrestrial ecosystems but reveals the general lack of reference sequence data for microorganisms, underscoring the value of using traditional sampling and taxonomic assignment methods. Environmental DNA sampling coupled with high‐throughput sequencing is increasingly recognized as a useful method for assessing biodiversity with potential applications in terrestrial environments. Rock pools on granite inselbergs support diverse aquatic communities, yet the application of eDNA to document their biodiversity is lacking. Through a collaborative study with Indigenous communities, we investigated the effectiveness of eDNA metabarcoding alongside traditional sampling methods in characterizing the species richness and composition of eukaryotes in 15 rock pools across southeastern Australia.